PENGARUH RELATIONSHIP MARKETING TERHADAP CUSTOMER RETENTION DAN CUSTOMER LOYALTY (Studi Empiris pada Nasabah Bank Central Asia Cabang Madiun) - Kurniawati, Dyah (Widya Warta, 2019)
The purpose of this study was to analyze (1) the direct effect of relationship marketing on customer retention and customer loyalty, (2) the effect of customer retention on customer loyalty, (3) the indirect effect of variable relationship marketing on customer loyalty through customer retention. The samples in this study were BCA customers at Madiun Branch with accidental sampling techniques. The results of the study found that relationship marketing directly affected customer retention and customer loyalty in a positive direction. Customer retention had an immediate effect on customer loyalty, and relationship marketing had an indirect effect on customer loyalty through customer retention.